Information threats and information attacks: Problem, solution, recommendations - Jamshid Yaxshiboyevich Oripov (Research Parks Publishing LLC, 2020)
In this article, the author provides general recommendations and suggestions on information threats and information attacks, their similarities and differences, and important aspects of the formation of immunity to risks in young people.